Pemilihan Jenis Tanaman Kebun-Talun: Suatu Kajian Pengambilan Keputusan oleh Petani - Suharjito, Didik (Institut Pertanian Bogor (IPB University), 2002)
A study of peasant's choices to agriculture crops is important to understand what is its preferencies, consideration, and constraints. This knowledge of peasant' choices could help the scientists and extensionists for sharing their knowledges with the peasant communities to improve agriculture productivity, product optimalization, and products prices. The objective of the research is to explain what reasons/ consideration is taken into account by peasants when he choose a kind ofplant species. The research found that peasant choose kebuntalun crops with some reasons i.e. (1) to get numerous products; (2) to get various products (daily and continuously, for household subsistence and for income); (3) to be easy maintenance; (4) to be easy to sell products; (5) its price is stable or increase; (6) heritage from our parent; (7) small plot of land; (8) to be suitable with land condition. This finding show that the peasant has productive, efficient, and commercial orientation as well as prefer to diversity of products. Based upon this finding the author suggest that the role of extensionist is to provide basket ofplant choices which can be productive, efficient, easy to maintain, easy to sell, stable or increase price, and diversity ofplants.